Biomechanical Comparison of Syndesmotic Repair Techniques During External Rotation Stress. (November 2018) - Goetz, Jessica E.; Davidson, Nathan P.; Rudert, M. James; Szabo, Nicole; Karam, Matthew D.; Phisitkul, Phinit
Background: The purpose of this study was to compare mechanical behavior of conventional syndesmosis fixation devices with new anatomic repair techniques incorporating various repair augmentations to determine which approach would return rotational ankle mechanics closer to those of an intact ankle. Methods: Ten pairs of fresh-frozen through-the-knee cadaveric lower limbs were subjected to 7.5 Nm of external rotation torque while under 750 N of axial compression. After testing specimens intact and with the deltoid and syndesmotic ligament complexes completely destabilized, specimens underwent syndesmotic fixation using a screw, a suture button construct, a prototype structurally augmented flexible trans-syndesmotic fixation device, or the prototype device plus suture repairs of the anterior-inferior tibiofibular ligament and deep deltoid ligament. Syndesmotic repair devices were exchanged between tests so that each specimen was tested with 2 different fixation techniques. Whole-foot rotation angles at 7.5 Nm of applied torque were measured for comparison of the different repair strategies, and reflective markers mounted on the tibia, fibula, and talus were used to track translations and rotations of the talus and the fibula relative to the tibia during testing. Results: Syndesmotic destabilization significantly ( P < .001) increased whole-foot, talus, and fibula rotation in an axial plane and posterior fibula translation under 7.5 Nm of torque. Neither the suture button nor the augmented flexible trans-syndesmotic fixation device reduced those increases. Screw fixation or addition of anatomic ligament repairs to the augmented flexible fixation device successfully reduced axial plane rotations and sagittal plane translations to near intact levels. Conclusion: Flexible trans-syndesmotic fixation alone was found to be insufficient for restoring rotational stability to the ankle/talus or preventing sagittal plane displacement of the fibula. Clinical Relevance: Repairs to simulate anatomic structures disrupted during a syndesmosis injury were required to restore rotational stability to the foot when using flexible trans-syndesmotic fixation that may have clinical applicability.